(3GdQhVI GdRGgQI GdfjQI hGdLhgQI GdfGOQIs
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdYdGe hHYO agPG cJGH GdQhVI GdRGgQI GdfjQI GdfGFQI hGdLhgQI GdfGOQI GdeTJed ajg Ydhe GdOfjG hGdBNQI hde jcf deKdg TGf ef bOje hEdi GdBf hdG deKd eUfag ai YUQg EfSGf s
(3BNQgG (B:s
(3eKd GdbdH ceKd GdSdWGf ai GdhdGjI , dCf GdSdWGf MGce Ydi GdQYjI hGdNOe hGdbdH Ydi GdLhGQM hGdCYVGA QHfG Ydjc JhcdfG hEdjc CfHG hEdjc GdeUjQ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B538s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdMOjK h GdeUWdMs